Challenges following a personalised diet adhering to dietary guidelines in a sample of Australian university students. Issue 3 (September 2019) - Irwin, Christopher; Desbrow, Ben; Khalesi, Saman; McCartney, Danielle
Background: Food-based dietary guidelines are designed to support populations to adopt a healthy diet. University students studying nutrition related courses are typically en-route to professional roles that involve advocating a healthy diet. Aim: The present study compared the dietary intake of university students enrolled in a foundation nutrition course against the Australian Dietary Guidelines (ADGs) and Nutrient Reference Values (NRVs), and explored students' experiences of following a 3-day self-determined diet plan adhering to the ADGs/NRVs. Methods: Students ( n = 115) initially collected, and subsequently analysed a 3-day prospective diet record to determine food group/nutrient intake. Individuals then modified their diet to comply with recommendations (ADGs/NRVs) and attempted to implement the diet plan. Challenges associated with meeting the ADGs/NRVs were described in an online survey form. Results: Baseline food group and nutrient intakes deviated from the guidelines, with 'lean meats & alternatives' the only group consumed in recommended quantities. Students demonstrated the capacity to plan a modified personal diet adhering to the ADGs food group recommendations. However, when following this, several key challenges to dietary adherence were identified. Challenges were categorised as personal/behavioural factors (e.g. the quantity/type of food) and societal factors (e.g. time, cost, social factors). Conclusion: Overall, this study highlights challenges influencing adherence to dietary guidelines in a sample of undergraduate university students. Understanding these factors may help tailor advice to facilitate improved dietary patterns in this population group.